ONTROLE DE NEMATÓDEOS GASTRINTESTINAIS EM OVINOS: MÉTODO FAMACHA E CONTAGEM DE OVOS POR GRAMAS DE FEZES (OPG) - Gasparin, Bruna; Sasa, Aya; Garcia, Aracy; Da Silva, Ana Paula; Félix, Aldair (ANAIS DO ENIC, 2018)
-